Career & technical education [electronic resource] - MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; Skills Commons; The California State University; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 2020)
Quoted from the homepage:ePortfolios and Career & Technical Education: SkillsCommons has used multiple methods for capturing open educational practices in teaching, learning, and institutional ePortfolios. Structured video and podcast interviews with CTE program leaders to explain the innovations and successes of their workforce development programs. Storytelling methods that SkillsCommons customized for capturing the impact of innovations and successes of their workforce development programs. Reuse, Revise, & Remix strategies and examples showcasing open educational practices by CTE programs. Partner with commercial providers to reuse, revise, remix OER and improve the quality of learning experiences and outcomes. Explore the collection of over 50 institutional and teaching video and podcast ePortfolios that tell CTE stories of how, what, and why they changed to more innovative and successful learning and employability solutions for their diverse populations of students.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Electronic portfolios. .; College teaching -- Aids and devices -- Electronic portfolios. .; Universities and colleges -- Curricula -- Aids and devices -- Electronic portfolios. .; Technical education -- United States -- Aids and devices -- Virtual; Technology -- Study and teaching -- Virtual; Career education -- United States -- Aids and devices -- Virtual; Career academies -- Aids and devices -- Virtual; Professional education -- Aids and devices -- Virtual